Do Children go to Field? - The State of Outside-The-School Environmental Education in the Case of Downtown Budapest Schools (Global Journal of Human-Social Science, 2020)
In the rapidly evolving world of the 21st century, scientific knowledge is becoming more and more valuable. Today's engineering and technological developments are inconceivable without specialists with excellent scientific knowledge. But how can today's young people be interested in science? In our opinion, this is no longer possible with traditional methods, practiceoriented experiential pedagogy is needed for this, preferably in a natural environment. But what can a downtown school do if it wants to hold a science class outside the school building? We are looking for the answer to this in our study.
Keywords: out-of-school teaching; downtown schools; science; environmental education